GABAA Receptor Subtypes and the Abuse‐Related Effects of Ethanol in Rhesus Monkeys: Experiments with Selective Positive Allosteric Modulators. (8th April 2019) - Berro, Lais F.; Rüedi‐Bettschen, Daniela; Cook, Jemma E.; Golani, Lalit K.; Li, Guanguan; Jahan, Rajwana; Rashid, Farjana; Cook, James M.; Rowlett, James K.; Platt, Donna M.
Abstract : Background: Previous studies have investigated α1GABAA and α5GABAA receptor mechanisms in the behavioral effects of ethanol (EtOH) in monkeys. However, genetic studies in humans and preclinical studies with mutant mice suggest a role for α2GABAA and/or α3GABAA receptors in the effects of EtOH. The development of novel positive allosteric modulators (PAMs) with functional selectivity (i.e., selective efficacy) at α2GABAA and α3GABAA receptors allows for probing of these subtypes in preclinical models of the discriminative stimulus and reinforcing effects of EtOH in rhesus macaques. Methods: In discrimination studies, subjects were trained to discriminate EtOH (2 g/kg, intragastrically) from water under a fixed‐ratio (FR) schedule of food delivery. In oral self‐administration studies, subjects were trained to self‐administer EtOH (2% w/v) or sucrose (0.3 to 1% w/v) under an FR schedule of solution availability. Results: In discrimination studies, functionally selective PAMs at α2GABAA and α3GABAA (HZ‐166) or α3GABAA (YT‐III‐31) receptors substituted fully (maximum percentage of EtOH‐lever responding ≥80%) for the discriminative stimulus effects of EtOH without altering response rates. Full substitution for EtOH also was engendered by a nonselective PAM (triazolam), an α5GABAA ‐preferring PAM (QH‐ii‐066) and a PAM at α2GABAA, α3GABAA, and α5GABAA receptors (L‐838417). A partial (MRK‐696) or an α1GABAA ‐preferring (zolpidem) PAM only engendered partial substitution (i.e., 50 to 60% EtOH‐lever responding). In self‐administration studies, pretreatments with the functionally selective PAMs at α2GABAA and α3GABAA (XHe‐II‐053 and HZ‐166) or α3GABAA (YT‐III‐31 and YT‐III‐271) receptors increased EtOH, but not sucrose, drinking at doses that had few, or no, observable sedative‐motor effects. Conclusions: Our results confirm prior findings regarding the respective roles of α1GABAA and α5GABAA receptors in the discriminative stimulus effects of EtOH and, further, suggest a key facilitatory role for α3GABAA and potentially α2GABAA receptors in several abuse‐related effects of EtOH in monkeys. Moreover, they reveal a potential role for these latter subtypes in EtOH's sedative effects. Abstract : Studies in humans and mutant mice suggest a role for α 2GABAA and/or α 3GABAA receptors in ethanol's (EtOHs) behavioral effects. Novel ligands with functional selectivity at these receptor subtypes were used to probe their role in nonhuman primates. Results show that HZ‐166 (functional selectivity: α 2GABAA and α 3GABAA receptors) and YT‐III‐31 (functional selectivity: α 3GABAA receptors) mimic EtOHs discriminative stimulus effects (left) and enhance EtOH reinforcing effects (right), suggesting a facilitatory role for α 3GABAA, and potentially α 2GABAA, receptors in several abuse‐related effects of EtOH.